A High-Density Genetic Linkage Map for Cucumber (Cucumis sativus L.): Based on Specific Length Amplified Fragment (SLAF) Sequencing and QTL Analysis of Fruit Traits in Cucumber - Zhu, Wen-Ying; Huang, Long; Chen, Long; Yang, Jian-Tao; Wu, Jia-Ni; Qu, Mei-Ling; Yao, Dan-Qing; Guo, Chun-Li; Lian, Hong-Li; He, Huan-Le; Pan, Jun-Song; Cai, Run (Frontiers in Plant Science, 2016)
High-density genetic linkage map plays an important role in genome assembly and QTL ﬁne mapping. Since the coming of next-generation sequencing (NGS), makes the structure of high-density linkage maps much more convenient and practical, which simplifies SNP discovery and high-throughput genotyping. In this research, a high-density linkage map of cucumber was structured using specific length amplified fragment sequencing, using 153 F2 populations of S1000×S1002. The high-density genetic map composed 3,057 SLAFs, including 4,475 SNP markers on 7 chromosomes, and spanned 1061.19cM. The average genetic distance is 0.35cM. Based on this high-density genome map, QTL analysis was performed on two cucumber fruit traits, fruit length and fruit diameter. There are 15 QTLs for the two fruit traits were detected.